Improved Dynamic Postural Task Performance without Improvements in Postural Responses: The Blessing and the Curse of Dopamine Replacement - K. B. Foreman; C. Wisted; O. Addison; R. L. Marcus; P. C. LaStayo; L. E. Dibble (Parkinson's Disease)
Introduction. Dopamine-replacement medications may improve mobility while not improving responses to postural challenges and could therefore increase fall risk. The purpose of this study was to measure reactive postural responses and gait-related mobility of patients with PD during ON and OFF medication conditions. Methods. Reactive postural responses to the Pull Test and performance of the Functional Gait Assessment (FGA) were recorded from 15 persons with PD during ON and OFF medication conditions. Results. Persons with PD demonstrated no significant difference in the reactive postural responses between medication conditions but demonstrated significantly better performance on the FGA when ON medications compared to OFF. Discussion/Conclusion. Dopamine-replacement medications alone may improve gait-related mobility without improvements in reactive postural responses and therefore could result in iatrogenic increases in fall risk. Rehabilitation providers should be aware of the side effects and limitations of medication treatment and implement interventions to improve postural responses.